2005
DOI: 10.1021/ja0516514
|View full text |Cite
|
Sign up to set email alerts
|

Mesosynthesis of ZnO−Silica Composites for Methanol Nanocatalysis

Abstract: Methanol catalysis meets chemistry under confined conditions. Methanol is regarded as one of the most important future energy sources. ZnO/Cu composite materials are very effective in heterogeneous catalysis for methanol production due to the so-called strong metal-support interaction effect (SMSI). Therefore, materials of superior structural design potentially representing model systems for heterogeneous catalysis are highly desired. Ultimately, such materials could help to understand the interaction between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
101
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 41 publications
4
101
0
Order By: Relevance
“…[16][17][18] The liquid ZnO-precursor [{H 3 CZnO-A C H T U N G T R E N N U N G (CH 2 ) 2 OCH 3 } 4 ] was prepared according to the literature. [8] The infiltration experiments were performed under exclusion of air and moisture by using Schlenk techniques, and the mesoporous carbon was carefully dried prior to use. Typically, 0.3 g of the mesoporous carbon powder was stratified with the liquid and undiluted [{H 3 CZnO-A C H T U N G T R E N N U N G (CH 2 ) 2 OCH 3 } 4 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18] The liquid ZnO-precursor [{H 3 CZnO-A C H T U N G T R E N N U N G (CH 2 ) 2 OCH 3 } 4 ] was prepared according to the literature. [8] The infiltration experiments were performed under exclusion of air and moisture by using Schlenk techniques, and the mesoporous carbon was carefully dried prior to use. Typically, 0.3 g of the mesoporous carbon powder was stratified with the liquid and undiluted [{H 3 CZnO-A C H T U N G T R E N N U N G (CH 2 ) 2 OCH 3 } 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…[7] Recently, we were able to prepare size-selected ZnO particles in the pores of ordered mesoporous silica materials. [8] The key to success in this preparation was the use of an innovative, organometallic-precursor system resembling ZnO on a molecular scale. [8,9] Due to the potentially large surface area, the idea is very tempting that the nanoporous material itself is composed of a matrix material that is catalytically more relevant than silica.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By embedding the catalytically active component into a well-defined superstructure (e.g., a hierarchically structured mesoporous matrix), it should be possible to simultaneously simplify and miniaturize the supported catalyst [14][15][16][17][18][19][20] and to utilize in the preparation the favorable effects of the spatially confined reaction conditions on the chemistry occurring in the porous solid [21]. However, this approach carries the risk of interference by the pore walls of the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…507 Polarz et al reported the preparation of nanocrystalline, size-selected ZnO inside the pore system of ordered mesoporous silica materials. 508 Highly defined materials containing nanocrystalline ZnO may be interesting as new model systems for methanol catalysis. Sen et al reported the templateassisted fabrication of magnetic mesoporous silicamagnetite nanocomposites 509 which are capable of binding DNA or eluting DNA, and also can be used to extract RNA from bacterial cells.…”
Section: Use Of Confined Spacesmentioning
confidence: 99%